Structural, Microstructural and Electrical Properties of Strontium Barium Niobate (SBN60) Ceramics. (2015) - Mathivanan, V.; Raj, S. Gokul; Kumar, G. Ramesh; Mohan, R.
Abstract: Tungsten bronze type Sr0.6 B0.4 Nb2 O6 ceramics were synthesized by solid state process. Cerium was used as dopant to improve its electrical properties. Single phase nature of the SBN60 composition were obtained successfully by this method in were confirmed through powder X-ray diffraction anlaysis. Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy with energy dispersive X–ray (SEM/EDX) and photoluminescence (PL) spectrometry were carried out to investigate its vibrational and surface phenomena which occurs during sintering. Dielectric measurements were carried out for pure and Ce doped SBN60. The obtained results were discussed in detail.